[Rezension von: Snyman, Fanie, 1954-, Historical commentary on the Old Testament, Malachi] - Kessler, Rainer (Acta theologica, 2016)
Fanie Snyman, from the University of the Free State in Bloemfontein, South Africa, is one of the best known researchers in the field of Old Testament prophecy. He published articles on Jeremiah and on some of the so-called Minor Prophets, viz. Amos, Obadiah, Habakkuk, and Zephaniah. The bulk of his studies in this area, however, explore Malachi. The number may not be complete, but I counted seven essays on nearly every pericope of the short book. The list begins with a study on “Antitheses in Malachi 1:2-5”, which appeared in the Zeitschrift für die alttestamentliche Wissenschaft (1986), and ends with a paper on “Malachi 4:4-6 (Heb. 3:22-24) as a point of convergence in the Old Testament or Hebrew Bible”, published in 2012 in HTS Teologiese Studies/Theological Studies. Obviously, his articles covered the entire text of the book.